2007
DOI: 10.1021/ja0715142
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structure Revision of the Marine Metabolite Palmerolide A

Abstract: A unique natural product termed palmerolide A was recently isolated from the Antarctic marine tunicate Synoicum adareanum by Baker and coworkers. 1 The structure and absolute stereochemistry of palmerolide A, expressed by formula 1 (Scheme 1), was solved by NMR studies and reveals a 20-membered macrolide decorated with a poly-unsaturated N-acyl dienamine side chain distinct from the N-acyl enamine found in salicylihalamide and related natural products. 2 Palmerolide is a differential cytotoxin with an activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 20 publications
1
69
1
2
Order By: Relevance
“…[5,6] As part of our ongoing studies on the use of sulfoximines in metal catalysis, [7] we recently reported that C 1 -symmetric amino sulfoximines 1 and oxazolinyl sulfoximines 2 were effective ligands in asymmetric copper catalyses. [8][9][10] We now describe the use of sulfoximine 1 a in copper-catalyzed VMARs between various cyclic dienol silanes and ketonic electrophiles.…”
mentioning
confidence: 99%
“…[5,6] As part of our ongoing studies on the use of sulfoximines in metal catalysis, [7] we recently reported that C 1 -symmetric amino sulfoximines 1 and oxazolinyl sulfoximines 2 were effective ligands in asymmetric copper catalyses. [8][9][10] We now describe the use of sulfoximine 1 a in copper-catalyzed VMARs between various cyclic dienol silanes and ketonic electrophiles.…”
mentioning
confidence: 99%
“…In a synthetic approach toward the fascinating natural product (−)-zampanolide (68), l-serine methyl ester (64) was subjected to a one-pot reduction/VMAR for the construction of fragment 67 to avoid epimerization at the stage of the aldehyde (Scheme 2.16) [36]. The VMAR coupling was efficiently carried out via a three-step one-pot protocol [37], where 64 was first reduced to aldehyde 65 according to a racemization-free operation [DIBAL-H and TiCl 2 (O i Pr) 2 mixture] and the aldehyde was subjected in situ to the subsequent vinylogous aldol reaction.…”
Section: Ester-derived Silyl Dienol Ethers -Diastereoselective Processesmentioning
confidence: 99%
“…One of the most challenging approaches in this field is probably the total synthesis of palmerolide A (144). It is noteworthy that the independent and contemporaneous development of VMAR products 142 and 143 in 2007-2008 by Nicolaou [62,63] and De Brabander [64] demonstrates the extreme viability and sustainability of this process (Scheme 2.34). The VMAR of 140 with aldehyde 141 under the conditions described by Kobayashi produced hydroxy vinyl iodide 142 in 83% yield and 89% de.…”
Section: Total Synthesesmentioning
confidence: 99%
“…Indeed, VMAR has successfully been utilized in natural product syntheses by many groups [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] including ourselves. [21][22][23][24][25] However, a,b-unsaturated aldehyde is not generally a good substrate for VMAR in terms of yield (i.e., low to moderate).…”
mentioning
confidence: 99%